Mengdetrening vs høyintensitets intervalltrening - Andersen, M. K. S.; Bjørkavoll-Bergseth, M. F. (2010)
Sports medicine is a field in constant renewal. During the last century research has been done to improve the performance of elite athletes. Findings have led to new questions. One question today is regarding the optimal training program. Our goal with this report has been to make a review of traditional sports physiology and compare papers reporting training programs of high intensity training (HIT) and continous training on this background. METHOD: This assignment consists of two parts: first general endurance training physiology and then a evaluation and discussion of five articles comparing HIT and continous training, selected by predefined criteria. In the first part sources are textbooks and journal articles. DISCUSSION: Evidence suggested similar effects of HIT and endurance traning on changes in VO2-kinetics, cardiovascular variables and muscle enzymes. One study found similar competitional results after both training programs. Lack of time is often reported as the main reason for low activity. Our main finding is that HIT is a highly time-efficient training method that leads to the same physiological changes as continous training. Therefore, it may be an alternative to consider for general recommendations. CONCLUSION: HIT and continous training lead to similar changes measured with cardiorespiratory variables. HIT is also a very time efficient training method compared to continous training, and could be an alternative for everyone from top athletes to the general population. There are, however, still questions remaining to be answered, for instance regarding differences between the training programs on long-term effects and possibly other variables still not studied.